Effects of Supply Chain Security on Supermarkets Performance in Kenya (A case of Nakumatt supermarkets in Nairobi) - Nanyama, Everlyne; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Ensuring a supply chain is secure from intentional as well as unintentional incidents is critical intoday’s global economy. This study conceptualized and develops four supply chain securitypractices (trading partner security, procedural security, physical security and access control)and tested the relationships between the supply chain security and the performance ofsupermarkets in Kenya. The research adopted a descriptive design. The population of the studyconsisted of 120 employees from all Nakumatt branches in Nairobi. The study employed acensus approach to collect data from the population of 120 respondents hence the study utilized100% of the target population. Data for the study was collected and the findings were used todetermine whether supply chain security can enhance supermarkets performance.Questionnaires were used as the main collection instrument and a pilot test was subsequentlycarried out to pre-test questionnaires for validity and reliability. The gathered data wasanalyzed using descriptive and inferential statistics aided by Statistical Package for SocialSciences (SPSS) version 20 and findings presented on tables, pie charts, figures and graphs.Correlation analysis and multiple regressions were used to establish the relationship betweenthe research variables. The findings of the study suggest that access control, procedural securityand physical security practices have a significant impact on supermarket performance. Thus thestudy recommended that management of the supermarkets should improve on provision ofsecurity awareness and training to its trading partners as this will help enhance the supply chainsecurity culture. Also Total Security Management philosophy should be initiated to enhancesupply chain security.